Phytoremediation of Lead Contaminated Soil Using Sorghum Plant in Association with Indigenous Microbes - Iqra Tabassum; Sumaira Mazhar; Beenish Sarfraz (Scientific Inquiry and Review, 2022)
Heavy metals are discharged in large quantities in both land and water bodies, causing long-term damage to living organisms. Phytoremediation is an effective way to address this problem. The goal of this study was to identify how lead resistant microorganisms affect the growth of sorghum plant, both in the presence and absence of lead. For this purpose, lead resistant microbes were isolated to investigate the growth and concentration of lead in the sorghum plant. Isolated species were inoculated with lead containing media in different concentrations, such as 300, 400, 500, and 600 µg/ml concentrations. Highly lead resistant bacterial isolates were selected and inoculated with sorghum seeds under typical environmental conditions in small pots, with and without lead contamination (300 mg/Kg). In the presence of lead resistant bacteria, efficient growth was observed with less concentration of lead in the plants. Promising results were observed in the presence of GS3 and IS2 isolates. The current study showed that lead tolerant bacterial isolates are very helpful to degrade lead when grown with sorghum seeds. Furthermore, it also enhances the growth of sorghum plant.